2014
DOI: 10.1371/journal.pone.0098997
|View full text |Cite
|
Sign up to set email alerts
|

Energy Costs of Catfish Space Use as Determined by Biotelemetry

Abstract: Animals use dispersed resources within their home range (HR) during regular day-to-day activities. The high-quality area intensively used by an individual, where critical resources are concentrated, has been designated as the core area (CA). This study aimed to describe how animals utilize energy in the HR and CA assuming that changes would occur according to the size of the used areas. We observed energetic costs of space use in the largest European freshwater predator catfish, Silurus glanis, using physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Previous catfish stocking experiments in Czech reservoirs have shown that catfish respond to conditions surpassing ecological carrying capacity with extended movements, declines in growth and high catchability to angling gear, indicating intensive foraging in their new environment (Vejřík et al, 2017, 2019). Also, in previous work catfish have been found to be stressed by social competition (Carol et al, 2007; Slavík & Horký, 2009; Slavík et al, 2014), and are also challenged by finding shelter among unfamiliar individuals (Slavík, Horký, Maciak, & Wackermannová, 2016). Alternatively, because the translocated catfish were relatively large‐bodied, even the smallest catfish that we stocked unlikely experienced substantial risk of predation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous catfish stocking experiments in Czech reservoirs have shown that catfish respond to conditions surpassing ecological carrying capacity with extended movements, declines in growth and high catchability to angling gear, indicating intensive foraging in their new environment (Vejřík et al, 2017, 2019). Also, in previous work catfish have been found to be stressed by social competition (Carol et al, 2007; Slavík & Horký, 2009; Slavík et al, 2014), and are also challenged by finding shelter among unfamiliar individuals (Slavík, Horký, Maciak, & Wackermannová, 2016). Alternatively, because the translocated catfish were relatively large‐bodied, even the smallest catfish that we stocked unlikely experienced substantial risk of predation.…”
Section: Discussionmentioning
confidence: 96%
“…We expected the behaviour of northern pike and catfish to be symptomatic of competitive interactions following introduction. Both catfish and pike are known to show agonistic behavioural interactions towards conspecifics (Nilsson, 2006; Slavík, Horký, & Závorka, 2014) and should therefore experience interference competition with resident conspecifics. Although catfish has been described as temporarily social (Boulêtreau et al, 2016), territoriality is a well known phenomenon, resulting in confined home ranges that vary seasonally in dimension (Brevé et al, 2014; Carol, Zamora, & García‐Berthou, 2007; Slavík & Horký, 2009; Slavík et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High activity and SMR are traits typically related to high‐gain high‐cost strategies, which are expected to be successful in a predictable environment with rich food resources (Biro & Stamps ). Therefore, it is likely that these three traits were associated with territorial behavior, where territorial individuals defend a small habitat patch, display high activity and SMR, whereas non‐territorial floaters and wanderers display low activity and SMR (Jenkins ; Dingemanse & de Goede ; Careau & Garland ; Slavík, Horký & Závorka ). There was no relationship between SGR in body length and AS, but AS was positively correlated with SGR in body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Territorial individuals as opposed to non‐territorial ones are often highly active and aggressive, have high metabolic rates, and maintain a stable position within the habitat patch they defend (e.g. great tit, Parus major : Dingemanse & de Goede ; European catfish, Silurus glanis : Slavík, Horký & Závorka ). Non‐native invaders can induce an additional competitive pressure (Fausch & White ; Cole & Harris ) and reduce the predictability of resource distribution (Carpenter et al .…”
Section: Introductionmentioning
confidence: 99%